2019
DOI: 10.3390/ijerph16101863
|View full text |Cite
|
Sign up to set email alerts
|

Hot and Cold Spot Areas of Household Tuberculosis Transmission in Southern China: Effects of Socio-Economic Status and Mycobacterium tuberculosis Genotypes

Abstract: The aims of the study were: (1) compare sociodemographic characteristics among active tuberculosis (TB) cases and their household contacts in cold and hot spot transmission areas, and (2) quantify the influence of locality, genotype and potential determinants on the rates of latent tuberculosis infection (LTBI) among household contacts of index TB cases. Parallel case-contact studies were conducted in two geographic areas classified as “cold” and “hot” spots based on TB notification and spatial clustering betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Tuberculosis (TB) continues to be a global concern because of its high infectivity, mortality, and cost of therapy. In addition, the patients´ families are confronted with extra social and clinical burdens associated with TB disease [ 9 ]. There is an increasing awareness of the problem LTBI poses to HHCs and therefore the need to protect such at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) continues to be a global concern because of its high infectivity, mortality, and cost of therapy. In addition, the patients´ families are confronted with extra social and clinical burdens associated with TB disease [ 9 ]. There is an increasing awareness of the problem LTBI poses to HHCs and therefore the need to protect such at-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the obvious imbalance of the ethnicity and economic levels between cold and hot spots, the variables of ethnicity and income are not comparable. [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the SNPs distance between the two strains would become larger. Our study also performed contact tracing among included cases [39]. The results showed that the detection rate of TB in household contacts was very low.…”
Section: Discussionmentioning
confidence: 96%